2015
DOI: 10.5567/pharmacologia.2015.264.272
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment Evaluation of the Side Effects of Methanol Leaf Extract from Paullinia pinnata (Linn.), an Antityphoid Plant

Abstract: Background and Objective: Paullinia pinnata is an African woody vine whose leaf decoction has been used in Cameroon for the treatment of bacterial infections like typhoid fever, syphilis, gonorrhea, diarrhoea and symptoms such as stomach-ache and waist pain. The present study was designed to evaluate the adverse side effects resulting from the use of P. pinnata methanol leaf extract in the treatment of Salmonella typhimurium-induced typhoid in Wistar rats. Methodology: After the establishment of infection by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…number of human cancer cell lines [35]. e identification of new constituents in P. pinnata leaf extract adds to the existing data that emphasize the presence of numerous bioactive compounds isolated and characterized [20][21][22]24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…number of human cancer cell lines [35]. e identification of new constituents in P. pinnata leaf extract adds to the existing data that emphasize the presence of numerous bioactive compounds isolated and characterized [20][21][22]24].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the worse selectivity indices at concentrations tested. e in vivo toxicity test has shown that P. pinnata extract was not toxic at doses up to 200 mg/kg [24,42]. One should observe that the results of in vitro toxicity evaluation differ substantially from that observed in vivo.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Paullinia pinnata Linn (Sapindaceae) family is an important medicinal plant used in many indigenous medical systems for the treatment of infectious diseases 24 . Several studies revealed antibacterial and antidiarrheal activities of extracts and isolated compounds from P. pinnata [25][26][27][28][29][30] . D. multiflora and P. pinnata have shown promising antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%